Conditioning of surfaces by macromolecules and its implication for the settlement of zoospores of the green alga Ulva linza - Thomé, Isabel; Grunze, Michael; Rosenhahn, Axel (Biofouling, 2012)
Conditioning, ie the adsorption of proteins and other macromolecules, is the first process that occurs in the natural environment once a surface is immersed in seawater, but no information is available either regarding the conditioning of surfaces by artificial seawater or whether conditioning affects data obtained from laboratory assays. A range of self-assembled monolayers (SAMs) with different chemical terminations was used to investigate the time-dependent formation of conditioning layers in commercial and self-prepared artificial seawaters. Subsequently, these results were compared with conditioning by solutions in which zoospores of the green alga Ulva linza had been swimming. Spectral ellipsometry and contact angle measurements as well as infrared reflection absorption spectroscopy (IRRAS) were used to reveal the thickness and chemical composition of the conditioning layers. The extent that surface preconditioning affected the settlement of zoospores of U. linza was also investigated. The results showed that in standard spore settlement bioassays (45-60 min), the influence of a molecular conditioning layer is likely to be small, although more substantial effects are possible at longer settlement times.
Gesehen am 03.05.2018